2016
DOI: 10.1002/da.22484
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study (Gwas) and Genome-Wide by Environment Interaction Study (Gweis) of Depressive Symptoms in African American and Hispanic/Latina Women

Abstract: Background Genome-wide association studies (GWAS) have been unable to identify variants linked to depression. We hypothesized that examining depressive symptoms and considering gene-environment interaction (G×E) might improve efficiency for gene discovery. We therefore conducted a GWAS and genome-wide environment interaction study (GWEIS) of depressive symptoms. Methods Using data from the SHARe cohort of the Women’s Health Initiative, comprising African Americans (n=7179) and Hispanics/Latinas (n=3138), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
106
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(120 citation statements)
references
References 87 publications
(89 reference statements)
10
106
4
Order By: Relevance
“…Using LD score regression, we found that the genetic overlap between dependent life events and MDD (0.60) was nominally higher than for independent life events (0.20). This is in line with the findings by Dunn et al who found a strong genetic correlation between MDD and SLEs in women (r G =0.95) 23 . The genetic overlap between SLEs and MDD calls for a different interpretation of the effect of SLEs on MDD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Using LD score regression, we found that the genetic overlap between dependent life events and MDD (0.60) was nominally higher than for independent life events (0.20). This is in line with the findings by Dunn et al who found a strong genetic correlation between MDD and SLEs in women (r G =0.95) 23 . The genetic overlap between SLEs and MDD calls for a different interpretation of the effect of SLEs on MDD.…”
Section: Discussionsupporting
confidence: 93%
“…When personal SLEs were analysed modelling both genetic and environmental components, the SNP heritability estimate was significant and accounted for 8% of the variance in SLEs. This is the same as the estimate derived from the population-based study of African American women that found the SNP heritability of SLEs to be 8% 23 . However, another study found SNP effects account for roughly a third of variance in SLEs 22 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A second notable link between psychiatric disease and altered DCC epigenetics is an increase of about 50% in DCC gene expression in the prefrontal cortex of antidepressant-free patients with major depressive disorder who committed suicide [29], a finding later replicated [53]. In fact, there is now substantial correlational genetic evidence from human populations that variation in DCC expression is a risk factor for depression [29,53,7982]. Although such evidence lacks a causative link, using a mouse model of depression we have recently shown that increased Dcc expression in the prefrontal cortex induces susceptibility to developing depression-like phenotypes [53].…”
Section: Variations In DCC Receptor Expression Are Linked To Psychiatmentioning
confidence: 99%